1998
DOI: 10.1021/jo981280s
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure Parameters and Predictions of Enthalpies of Formation for Catacondensed and Pericondensed Polycyclic Aromatic Hydrocarbons

Abstract: Simple procedures that combine calculated ab initio theoretical energies with empirical structural parameters to correlate experimental enthalpies of formation for polycyclic aromatic hydrocarbons are evaluated for predictive potential. The analyzed data set consists of every benzenoid PAH with an experimentally determined DeltaH(f) degrees (g), i.e., nine catacondensed and three pericondensed aromatic compounds. The tested levels of theory use optimized STO-3G, 3-21G, and 6-31G calculated HF electronic energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…The calculations performed by Yu et al [42] using B3LYP/6-31G(d) and the atom-centred group method, lead to a theoretical value of heat of formation of coronene just in the middle of the interval between our experimental and theoretical result for this property. Data of Herndon et al, who predicted the heat of formation of this molecule by using the parametrized MP2 model at the MP2/6-31G * //HF/6-31G * level of theory [43], are also in good agreement with our results. In contrast, molecular mechanics calculations [44] and comparative molecular field analysis [45] appear to overestimate the heat of formation of this molecule.…”
Section: Theoretical Gas Phase Enthalpy Of Formationsupporting
confidence: 92%
See 1 more Smart Citation
“…The calculations performed by Yu et al [42] using B3LYP/6-31G(d) and the atom-centred group method, lead to a theoretical value of heat of formation of coronene just in the middle of the interval between our experimental and theoretical result for this property. Data of Herndon et al, who predicted the heat of formation of this molecule by using the parametrized MP2 model at the MP2/6-31G * //HF/6-31G * level of theory [43], are also in good agreement with our results. In contrast, molecular mechanics calculations [44] and comparative molecular field analysis [45] appear to overestimate the heat of formation of this molecule.…”
Section: Theoretical Gas Phase Enthalpy Of Formationsupporting
confidence: 92%
“…297.0 (DZVP-GGA/PBE96) Schulman and Disch [22] 274.0 (MP2/6-31G * ) 293.3 (HF/6-311G ** ) 300.4 (B3LYP/6-311G ** ) Blanquart and Pitsch [41] 292.4 (G3MP2//B3) Yu et al [42] 291.2, 293.7 (B3LYP/6-31G) Herndon et al [43] 296.5 (HF/6-31G * ) 288.5 (MP2/6-31G * ) Herndon et al [44] 326.9 (MM) Welsh et al [45] 352.8 (CoMFA) Disch et al [46] 283.7 (STO-3G) 288.7 (6-31G * SCF) a This value is the weighted average l and its corresponding uncertainty r s and were calculated as l ¼ …”
Section: Enthalpy Of Sublimation By Quartz Crystal Microbalancementioning
confidence: 97%
“…(21) However, in 1969, Dewar and de Llano (6) showed, on the basis of a semi-empirical calculation, that the atomization energy had an error of 43 kJ · mol −1 . Recently, theoretical studies (7) indicated a similar error. Naphthacene is known to be sensitive to oxygen in solution.…”
Section: Discussionmentioning
confidence: 76%
“…(5) Theoretical studies (6,7) have suggested that the calorimetric value of the enthalpy of formation of naphthacene (tetracene) is incorrect. Combustion calorimetry of pentacene has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…These deviations are comparable to the uncertainties of the experimental values that are on the order of 2 kJ/mol. Herndon 100 and co-workers have extensively used group additivity approaches in conjunction with quantum chemical methods. They used the semiempirical AM1 method, 97 the DFT method B3LYP, 90,91 and the ab initio MP2 theory 98 to determine enthalpies of formation for many common PAHs.…”
Section: Introductionmentioning
confidence: 99%